Analisis Gaya Bahasa dan Retorika dalam Pidato Joko Widodo pada Kongres 6 PAN 2024 di Channel Youtube Tribunnews - Viera Pramestya Makuta (STIKes Ibnu Sina Ajibarang, 2025)
In this study, the researcher analyzed the language style and rhetoric in Joko Widodo's speech. The purpose of this study is to describe the use of language style and rhetoric in Joko Widodo's speech. The method used in this study is descriptive qualitative. The data collection technique used is watch, listen, and note. The results of this study Joko Widodo's speech at the 6th Congress of the National Mandate Party (PAN) contains various elements of language style and rhetorical techniques that are effective in conveying political messages and raising the spirit of togetherness. The language style used by Jokowi tends to be simple, straightforward, and easy to understand, which allows the speech to be accepted by a diverse audience. In his speech, Jokowi uses rhetorical techniques such as anaphora, personal narratives, and optimism. Persuasive rhetoric that emphasizes the importance of synergy between political parties, government, and society. Jokowi also builds an ethos as a leader who is simple and close to the people, strengthening credibility and public trust. Overall, this speech not only aims to convey information, but also to motivate and arouse the emotions of the audience to contribute to national development.